A STUDY ON THE INDIGENOUS DEVELOPMENT OF POUR POINT DEPRESSANTS FOR WAXY CRUDES - ALI, SAPIAH (2013)
The production of waxy crude from offshore is coupled with flow assurance challenges due to high pour point of the crude and low temperatures. Below the wax appearance temperature (WAT), wax crystallizes out of the liquid hydrocarbon, which causes the gelation ofoil and increase in viscosity. As a result wax deposition will not only reduce the effective flow area but can also lead to complete pipeline blockage in certain cases. In order to nmiimize the associated problems for waxy crudes production from offshore fields assisted by pour point depressants (PPDs), extensive study is required for the better understanding and limitations of the involved mechanism. Currently there is no appropriate route map available for PPDs selection and formulation techniques for offshore production.